Antibacterial and herbicidal activity of ring-substituted 2-hydroxynaphthalene-1-carboxanilides - Gonec, Tomas; Kos, Jiri; Zadrazilova, Iveta; Pesko, Matus; Govender, Rodney; Keltosova, Stanislava; Chambel, Barbara; Pereira, Diogo; Kollar, Peter; Imramovsky, Ales; O'Mahony, Jim; Coffey, Aidan; et al. (Molecules, 2013)
In this study, a series of twenty-two ring-substituted 2-hydroxynaphthalene-1‑carboxanilides were prepared and characterized. Primary in vitro screening of the synthesized compounds was performed against Staphylococcus aureus, three methicillin-resistant S. aureus strains, Mycobacterium marinum, M. kasasii, M. smegmatis. and M. avium paratuberculosis. The compounds were also tested for their activity related to inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. 2-Hydroxy-N-phenylnaphthalene-1-carboxanilide and 2-hydroxy-N-(3-trifluoromethylphenyl)naphthalene-1-carboxamide (IC₅₀ = 29 µmol/L) were the most active PET inhibitors. Some of tested compounds showed the antibacterial and antimycobacterial activity against the tested strains comparable or higher than the standards ampicillin or isoniazid. Thus, for example, 2-hydroxy-N-(3-nitrophenyl)naphthalene-1-carboxamide showed MIC = 26.0 µmol/L against methicillin-resistant S. aureus and MIC = 51.9 µmol/L against M. marinum, or 2-hydroxy-N-phenylnaphthalene-1-carboxamide demonstrated MIC = 15.2 µmol/L against M. kansasii. The structure-activity relationships for all compounds are discussed.
Keywords: Mycobacterium; herbicidy; mikrobiální testy citlivosti; Structure-Activity Relationship; Photosynthesis; Naphthols; Anti-Bacterial Agents; Chloroplasts; fotosyntéza; transport elektronů; methicilin rezistentní Staphylococcus aureus; Spinacia oleracea; Microbial Sensitivity Tests; chloroplasty; vztahy mezi strukturou a aktivitou; Electron Transport; naftoly; antibakteriální látky; Herbicides; Methicillin-Resistant Staphylococcus aureus